Electrocatalytic CO2 reduction to C2+ products by non-Cu-based electrocatalysts: challenges and perspectives - Yuhang Ye; Chaoyu Ren; Zichao Xi; Qiao Chen; Ho Seok Park; Huanyu Jin; Hui-Ming Cheng (JPhys Energy)
Electrocatalytic CO _2 reduction reaction (eCO _2 RR) for C _2+ product generation is crucial for advancing clean energy conversion technologies. Cu-based electrocatalysts have long been regarded as the benchmark for producing C _2+ products by their moderate adsorption energy for key intermediates and strong C–C coupling capabilities. However, limitations such as poor stability and low selectivity have driven the search for non-Cu-based alternatives. In this review, we carefully analyze the recent progress in non-Cu-based electrocatalysts for eCO _2 RR. We identify that the CO _2 activation and adsorption behavior of intermediates significantly influence the C–C coupling steps. Considering this foundation, we propose three non-Cu-based electrocatalysts for C _2+ products: frustrated Lewis acid-base pair catalyst, chiral catalyst, and molecular catalyst. These catalysts show significant potential for C _2+ products generation and expanding the catalytic landscape beyond Cu-based systems. Finally, we discuss the current challenges and future directions of this emerging field. This review aims to provide a comprehensive overview and valuable insights to guide future research efforts in developing novel electrocatalysts, contributing to the advancement of sustainable energy applications.